2020
DOI: 10.4103/jispcd.jispcd_273_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vision in gnathological and orthodontic patients with temporomandibular disorders: A prospective experimental observational cohort study

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Specifically, associations were found between functional or skeletal orthognathic changes and oculomotor dysfunction. However, the type of relationship could not be determined [ 43 ].…”
Section: The Relationship Between Organ Of Vision and Stomatognathic System Dysfunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, associations were found between functional or skeletal orthognathic changes and oculomotor dysfunction. However, the type of relationship could not be determined [ 43 ].…”
Section: The Relationship Between Organ Of Vision and Stomatognathic System Dysfunctionsmentioning
confidence: 99%
“…The biochemical linkages discussed above may explain structural changes in individuals with ocular pathologies (ocular convergence defects vs. lateral mandibular deviation [ 39 ], astigmatism vs. crossbite [ 40 ], myopia vs. Class II division 1 malocclusion [ 41 ]). Bollero et al (2017) noted ocular motor defects versus crossbite and midline deviation [ 42 ], and that there is a correlation between TMDs occurrence and visual impairment prevalence [ 43 ] ( Figure 3 ).…”
Section: Biochemical Connectionmentioning
confidence: 99%
“…Vompi et al (19) observed a significant correlation between temporomandibular disorders (TMDs) and visual impairment. The study identified correlations between oculomotor dysfunction and orthognathic alterations, namely those related to function or skeletal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Cuccia and Caradonna [ 32 ] found similar observations in patients with temporomandibular joint displacements. Vompi and colleagues [ 116 ] also reported on 100 TMD patients a significant increase in ocular convergence insufficiency but also ocular deviation such as phorias and tropias as well as astigmatism compared to controls. Similar observations were made with dental malocclusion concerning tropia, phoria, ocular convergence defects, astigmatism, and myopia [ 117 ].…”
Section: Post Traumatic Craniocervical Disorders Reviewed From a Post...mentioning
confidence: 99%